Methodology for the optimal design of an integrated sugarcane distillery and cogeneration process for ethanol and power production. (15th December 2016) - Bechara, Rami; Gomez, Adrien; Saint-Antonin, Valérie; Schweitzer, Jean-Marc; Maréchal, François
Abstract: The application of systematic methodologies for the optimal design of integrated processes has seen increased interest in literature, namely for bioprocesses. The development and application of such a methodology to ethanol and power production from sugarcane and leaves, in a combined distillery and cogeneration plant is investigated in this article. The methodology breaks down as follows: process simulation, heat integration and thermo-economic evaluation, bi-objective multi-variable evolutionary optimization, and process selection. The objective functions are exergy efficiency and capital cost, whereas the selection criterion is the maximization of the Net Present Value (NPV). This choice was motivated by the variation in process related market parameters and their impact on profitability. Optimization generated 31 optimal trade-off solutions with better results than literature. Exergy efficiency ranged between 37.6% and 41.7% and capital costs between 155 M$ and 210 M$. Process selection led to a single configuration maximizing NPV for four economic scenarios. The configuration's exergy efficiency and capital costs were equal to 40.63% and 163 M$. This point presented an optimal compromise between heat integration and capital costs. This article provides a breakthrough in the application of this methodology, to the investigated process specifically. Highlights: Methodology for optimal design of sugarcane to ethanol and power plant. Process simulation, heat integration and thermo-economic evaluation model. Bi-objective multi-variable evolutionary optimization and analysis of results. NPV maximization for selecting point for different economic scenarios. Analysis and characterization of optimal point.